Support vector regression-based model for prediction of behavior stone column parameters in soft clay under highway embankment - Aljanabi Q.A.; Chik Z.; Allawi M.F.; El-Shafie A.H.; Ahmed A.N.; El-Shafie A. (Springer London, 2023)
Clay; Embankments; Forecasting; Highway engineering; Mean square error; Settlement of structures; Vectors; Mathematical procedures; Root mean square errors; Settlement behaviors; Settlement prediction; Settlement prediction models; Soft clays; Stone column; Support vector regression (SVR); Support vector machines